Situación alimentaria y nutricional en Colombia desde la perspectiva de los determinantes sociales de la salud (2013)
ABSTRACT: The World Health Organization has proposed the theoretical framework of social determinants of health to research and take action to reduce inequities in health status across regions, countries, groups and social classes. In this paper we propose a scheme for the study of food and nutrition situation in Colombia from the perspective of the social determinants of health, assuming it as the result of processes and phenomena of global and local scope. We also present information on several socio economic factors in order to clarity and highlight its relevance on both the determination as well as the distribution process of nutritional situation in Colombia. Data were drawn from secondary sources, especially from international institutions working on the social, food and agriculture realms and national governmental and non-governmental institutions.